Análisis de usabilidad y accesibilidad en las metodologías de desarrollo mediante aplicación web - Palomeque Espinoza, Leiver Oswaldo (My University, 2019)
In the present technological era it is important that a web application is developed under certain standards and meets certain expectations that the client demands; Thus, the issue of usability and accessibility is an arduous task and with a major impact on their development. There are many traditional and agile methodologies that help this work; such as XP, SCRUM, RUP, SNAIL. The usability and accessibility are considered as key indicators to measure the degree of use of the different softwares in the devices or objects that are available in the global market. Software development companies have the obligation to resort to methodologies that help meet the requirements given by users and in turn comply with the requirements that the standards provide. The present work, prior to obtaining the title of Systems Engineer, is to analyze the usability and accessibility of the methodologies through the use of a web application, which performs an analysis of the metrics determining decrease, permanence or increase in the degree of usability and accessibility of methodologies in application development.
En la presente era tecnológica es importante que una aplicación web sea desarrollada bajo ciertos estándares y cumpla ciertas expectativas que el cliente exige; es así que el tema de usabilidad y accesibilidad es una tarea ardua y con una incidencia mayúscula en el desarrollo de las mismas. Existen muchas metodologías tradicionales y ágiles que ayudan a esta labor; tales como XP, SCRUM, RUP, SNAIL. La usabilidad y accesibilidad se consideran como indicadores clave para medir el grado de uso de los diferentes softwares en los aparatos u objetos que se dispone en el mercado global. El presente trabajo, previo a la obtención del título de Ingeniero de Sistemas, es analizar la usabilidad y accesibilidad de las metodologías mediante la utilización de una aplicación web, la cual realiza un análisis de las métricas determinando descenso, permanencia o incremento del grado de usabilidad y accesibilidad de las metodologías en el desarrollo de aplicaciones.
Keywords: ACCESIBILIDAD; METODOLOGÍA; DESARROLLO; APLICACIÓN WEB